In vitro angiotensin-converting enzyme (ACE) inhibition activity of syzygium polyanthum leaves and its inhibition mechanism - Ismail, Azlini; Mohamed Suffian, Izzat Fahimuddin; Omar, Muhammad Nor; Abdul Hamid, Azzmer Azzar; Tuan Anuar, Tuan Ashraf Faiz (2021)
This PDF contains 18-pages of slides which has been presented by the inventor while participating in the 34th Scientific Meeting of the Malaysian Society of Pharmacology and Physiology, from 15th-17th July 2021